1992
DOI: 10.1152/ajprenal.1992.262.5.f744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an acute saline infusion on fluid and electrolyte metabolism in humans

Abstract: Several hormonal systems participating in body fluid and electrolyte homeostasis were investigated in six healthy volunteers in a supine body position during a period of 9 days and nights. Under strictly controlled conditions, striking circadian rhythms were observed for plasma levels of vasopressin, renin, aldosterone, guanosine 3',5'-cyclic monophosphate, cortisol, and epinephrine. Nocturnal decreases and diurnal increases in urine flow rate and urinary excretion of electrolytes were observed and closely par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1
9

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 0 publications
5
54
1
9
Order By: Relevance
“…Thus the present results are consistent with the hypothesis that urodilatin is a more likely mediator of the radiocontrast-induced natriuresis in this situation than atrial natriuretic peptide. This is in agreement with other investigations which indicate that urodilatin may be a particularly powerful paracrine regulator of renal sodium excretion [8,16,17].…”
Section: Figsupporting
confidence: 93%
“…Thus the present results are consistent with the hypothesis that urodilatin is a more likely mediator of the radiocontrast-induced natriuresis in this situation than atrial natriuretic peptide. This is in agreement with other investigations which indicate that urodilatin may be a particularly powerful paracrine regulator of renal sodium excretion [8,16,17].…”
Section: Figsupporting
confidence: 93%
“…Similarly, we did not observe changes in renin after sitting, but different findings have been reported concerning possible circadian effects. Previous investigations that maintained a supine posture throughout the day found that renin was lower in the afternoon (10,22), but a previous study in which seated posture was maintained also found no change in plasma renin activity (21). Plasma angiotensin II was significantly different after SEAT between the sexes; women increased and men decreased angiotensin II.…”
Section: Discussionmentioning
confidence: 78%
“…There were no changes in vasopressin levels after SEAT even though the men had, consistent with a previous investigation of sitting (21), a slight reduction in serum osmolality which might be expected to cause lower vasopressin (3). Perhaps a longer period of sitting or inactivity might have affected vasopressin as another study found reduced concentration in the afternoon in men in supine posture (10).…”
Section: Discussionmentioning
confidence: 99%
“…This threshold volume has previously been identified to be of clinical relevance for isotonic saline influx [17]. Volume and chloride overload can lead to pulmonary edema, hyperventilation, hyperchloremic acidosis, reduced glomerular filtration rate (up to 15%), suppression of the renin-angiotensin system (up to 60%), hypotension, impaired myocardial function and abdominal pain [16][17][18][26][27][28]. The symptoms we observed were transient, only mild to moderate and did not require extensive treatment.…”
Section: Resultsmentioning
confidence: 59%